Telco recommendation based on speed test data - Chia, Zhen Yik (2023)
The project focuses on the telco recommendation using collected data in Kampar hotspot area such as the hostel for the student and Universiti Tunku Abdul Rahman Kampar Campus. And this project is only used for academic purpose. It will provide students with data sciences analysis skill and knowledge, as well as networking knowledge. The telecom industry has vast volumes of data, maybe more than any other institution on the planet. Capturing the insights from this unstructured dataset and generating business insights using data science skills is the battleground. It is one thing to have useful data obtained in a traditional fashion; it is quite another to translate that data to a commercial use case and make your firm millions of dollars. Today's telecom administrator's web page has an enormous number of options, making it increasingly difficult for a customer to choose his or her optimal item selection. Thus, this project aims to develop and carry out a telco recommendation system using collect data to be satisfied people today. Furthermore, the main function of this proposed system is to develop a systematic method that improves existing cellular network data collection and reporting, helping the world become more connected via cellular networks. Moreover, some telco has better service quality depending on the locations due to the network operator investing strategically in the different geographical areas to cater to different demographics. Hence, choosing the right telco becomes a dilemma. Thus, the project aims to develop a system to convenient today the in Kampar area, which recommends them a that has a better network speed test result based on the user location.Other than that, the dataset in this project will be implemented by data pre-preprocessing to let it become more precise, provide more exact data to the users, and also allow other people or companies to obtain data from our database, to lead the world become more connected via cellular networks. Besides that, the system will perform a calculation to the data from the collected data and show to the user such as providing the average of download scores, upload scores, and latency scores. So that, it will improve the accuracy of data to the user who is finding the accurate data on the network. Lastly, this project will provide the data visualization for the user, let the user can easily view all the data in each location in the Kampar area.